Bicycle helmet use patterns in Italy. A description and analysis of survey data from an Italian friends of cycling association. (November 2017) - Popa, Ioana; Ferraro, Ottavia E.; Orsi, Chiara; Morandi, Anna; Montomoli, Cristina
Highlights: The propensity to use a bicycle helmet increases with age and is higher among men. The use of a helmet is more likely related to have had a crash. The use of a helmet is more likely related to use sport bikes. People who cycle more than 60 kilometers per week are more likely to use helmet. People who do not cycle daily are more likely to use helmet. Abstract: Cycling is becoming one of the most popular forms of recreation and transport the world over, but cyclists still have a high level of vulnerability. A bicycle helmet is an important safety device available to cyclists, but little is known regarding possible determinants of helmet use among adults. This study aims at providing information on helmet usage patterns in Italy and identifying the factors associated with bicycle helmet use. Data on 2072 bicycle riders from an Italian friends of cycling association aged 18 years or older who had ridden a bicycle in the last month were collected using an ad-hoc questionnaire via the web. The sample was equally distributed among subjects who always, most of the time, sometimes, rarely, or never use a helmet. To evaluate the association among socio-demographic and bicycle use characteristics and helmet use, a multinomial logistic regression model was performed. The results show a higher propensity to use a helmet among males, riders coming from Central and Southern Italy, people who cycles more than 60 kilometres in a week, cyclists who have already had a crash, people who do not cycle daily or almost daily, riders of sport bikes. Moreover, the propensity to use a helmet increases with age. The survey provided a first step in approaching the lack of data on cycling behaviour and the wearing of a helmet in Italy.